Synthesis of new 6-substituent 2-phenyl and 2-(furan-2-yl)-3-phenyl-quinoline-4-carboxylic acid derivatives - Hajalsiddig, Tawassl Tajelsir Hassan; Saeed, Ahmed Elsadig Mohammed (European Journal of Chemistry, 2019)
A synthesis of substituted quinolines has been achieved by the Doebner reaction which is a three component coupling of arylaldehyde, p-amino-acetophenone and phenyl pyruvic acid. The products of 2,3-diary-6-acetyl-quinoline-4-carboxylic acids were obtained by Claisen Schmidt condensation reaction with aldehydes in the presence of sodium hydroxide in order to give the corresponding α,β-unsaturated carbonyls. The substituted α,β-unsaturated carbonyls were condensed with urea, thiourea, hydrazine, phenyl hydrazine, semicarbazide hydrochloride and ethanolamine to synthesized 2-pyrimidinone, 2-pyrimidinethion, pyrazoline-1-phenyl, pyrazoline, pyrazoline-1-carboxamide and 1,4-oxazepines derivatives, respectively, with good yields. The purity and identities of products were elucidated through thin layer chromatography (TLC), melting point and spectroscopic data (IR, 1H NMR, 13C NMR and LC-Mass).